Czekolada jako źródło związków bioaktywnych oddziałujących na organizm = Chocolate as a source of bioactive compounds acting on the organism - Skrajda, Marta; Dąbrowski, Grzegorz (Journal of Education, Health and Sport, 2015)
Skrajda Marta, Dąbrowski Grzegorz. Czekolada jako źródło związków bioaktywnych oddziałujących na organizm = Chocolate as a source of bioactive compounds acting on the organism. Journal of Education, Health and Sport. 2015;5(9):429-442. ISSN 2391-8306. DOI10.5281/zenodo.31046 http://dx.doi.org/10.5281/zenodo.31046 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A429-442 https://pbn.nauka.gov.pl/works/626991 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 15.09.2015. CZEKOLADA JAKO ŹRÓDŁO ZWIĄZKÓW BIOAKTYWNYCH ODDZIAŁUJĄCYCH NA ORGANIZM Chocolate as a source of bioactive compounds acting on the organism Marta Skrajda, Grzegorz Dąbrowski Katedra Przetwórstwa i Chemii Surowców Roślinnych Wydział Nauki o Żywności, Uniwersytet Warmińsko-Mazurski w Olsztynie Uniwersytet Warmińsko-Mazurski w Olsztynie Katedra Przetwórstwa i Chemii Surowców Roślinnych Pl. Cieszyński 1, 10-726 Olsztyn e-mail: marta.skrajda@uwm.edu.pl Streszczenie Czekolada jest jednym z najbardziej lubianych smakołyków wszech czasów. Jej historia sięga czasów Olmeków, czyli około 3 tysięcy lat. Początkowo spożywana jako napój, dopiero w XVII wieku przyjęła obecną formę. Na rynku dostępnych jest wiele rodzajów czekolad. W zależności od zawartości miazgi kakaowej wyróżnia się czekoladę gorzką (tzw. naturalną, 35-70% miazgi), deserową (do 50% miazgi), mleczną (nie mniej niż 25% miazgi) i białą (nie mniej niż 20% tłuszczu kakaowego). Ponadto każdy z tych rodzajów może występować w postaci nadziewanej czy z dodatkiem orzechów, owoców, nasion, itp. Czekolada krytykowana jest za zawartość nasyconych kwasów tłuszczowych i wysoką kaloryczność, ale jest doceniana za zawartość związków biologicznie aktywnych. Wśród tych związków wyróżnia się: polifenole (głównie flawonoidy), aminy biogenne (fenyloetyloamina), alkaloidy (teobromina, kofeina) oraz składniki mineralne (np. magnez, potas). Należy jednak pamiętać, że zawartość tych związków w czekoladzie jest determinowana: rodzajem czekolady (zawartość miazgi kakaowej, rodzaj dodatków), rodzajem i pochodzeniem ziarna, sposobem obróbki ziarna. Słowa kluczowe: czekolada, aktywność antyoksydacyjna, związki biologicznie aktywne. Abstract Chocolate is one of the most popular sweets of all time. Its history dates back to about 3,000 years, the times of Olmec people. It was originally used as a drink and took its present form in seventeenth century. On the market there are many types of chocolate. Depending on the content of cocoa liquor stand out dark (35-70% of cocoa liquor), dessert (50% cocoa liquor), milk (not less than 25% cocoa liquor) and white (no less than 20% cocoa butter) chocolate. Moreover, each of these kinds may be either filled or with addition of nuts, fruits, seeds, and exc. Chocolate is criticized for its saturated fatty acid content and a high caloric value, but is appreciated for its biologically active compounds. Among these compounds are distinguished: polyphenols (especially flavonoids), biogenic amines (phenylethylamine), alkaloids (theobromine, caffeine) and minerals (e.g. magnesium, potassium). The content of these compounds in chocolate is determined by: type of chocolate (content of cocoa liquor, type of additives), type and origin of the cocoa bean and its processing method. Key words: chocolate, antioxidant activity, biologically active compounds.